Analysis of blended learning effectiveness at senior high school during covid-19 pandemic - Ellynd Dwi Kurnia; Dadi Setiadi; Baiq Sri Handayani (Jurnal Pijar Mipa, 2022)
Blended learning is a solution to overcome the limitation of learning space, time, and source learning. This study describes the application of blended learning at Senior High School 2 Taliwang during the Covid-19 pandemic. The research method used is a descriptive research method with a qualitative approach. The subjects in this study were students of class X MIPA at Senior High School 2 Taliwang totaling 62 people consisting of 2 classes. Data collection used questionnaires, interviews, and document studies. The results showed that the application of blended learning during the Covid-19 pandemic is divided between face-to-face and online learning, consisting of three stages, namely planning, learning process, and evaluation. The planning stage of the teacher makes a learning schedule, divides teaching time between teachers, prepares learning devices, materials, learning activities, learning media, and evaluation. At the stage of the learning process, the teacher conducts learning interactions, explains the material, assigns assignments and exercises either directly through face to face or online through Google Forms and electronic applications such as WhatsApp.The evaluation stage is assessed through cognitive assessment (knowledge) through assignments or portfolios and affective assessment by assessing those who actively participate in learning and respond.